Kekuatan Makna Ungkapan Bijak Dalam Novel “Rindu” dan “Pukat” Karya Tere Liye: Kajian Semantik - Rahmawati H (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Language has an important position in human life, namely as a communication tool that connects individuals with each other. The irreplaceable role of language forces humans to be able to master language. Effective communication can be achieved if there is the same meaning between the communicator and the communicant regarding the message conveyed. The research aims to explain the form of wise expressions in the novels